2014
DOI: 10.1007/s10461-014-0755-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex Workers and Their Clients Among Australian Gay and Bisexual Men

Abstract: The prevalence and factors associated with being paid and paying for sex were explored in an online sample of Australian gay men. Sexual risk behavior among male sex workers and their clients was mainly related to being more sexually adventurous in general rather than male-to-male sex work specifically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 23 publications
(37 reference statements)
8
37
0
Order By: Relevance
“…This contention is supported by previous research, which found that condomless sex with clients was best-predicted by condomless sex with non-paying casual partners, with factors other than sex work driving risk practices 9. Condomless sex among male sex workers may be more about sexual adventurism or pleasure-seeking than about sex work itself 10. Nevertheless, while sex work may not relate directly to sexual risk that does not mean it is unrelated to factors that attract some men to risky practices, supported by our finding that male sex workers in our sample were three times as likely as non-sex workers to report injecting drug use.…”
Section: Discussionsupporting
confidence: 50%
“…This contention is supported by previous research, which found that condomless sex with clients was best-predicted by condomless sex with non-paying casual partners, with factors other than sex work driving risk practices 9. Condomless sex among male sex workers may be more about sexual adventurism or pleasure-seeking than about sex work itself 10. Nevertheless, while sex work may not relate directly to sexual risk that does not mean it is unrelated to factors that attract some men to risky practices, supported by our finding that male sex workers in our sample were three times as likely as non-sex workers to report injecting drug use.…”
Section: Discussionsupporting
confidence: 50%
“…Among MSM, economic motivations have been shown to be associated with engagement in transactional sex. 31 The current results indicate that in Latin America unemployment is associated with an increase in transactional sex among MSM. Latin America has experienced a significant recent increase in urban-to-rural migration 23 , and urbanization may be higher in Latin America than any other region of the world.…”
Section: Discussionmentioning
confidence: 53%
“…Since the early 1990s, but more clearly so since 2000, scholarship has begun to examine how criminalization (Baral et al 2015, Prestage et al 2014, Bastow 1996, Wong 1995cited in Dorais 2005, Highcrest and Maki 1992, and the stigma of sex work and same-gender sex (Baral et al 2015), can increase the vulnerability of male sex workers and their clients to HIV and other STIs. In 1995, the Asian Community AIDS Services published its needs assessment of Asian sex workers in the Toronto-area, drawing a link between the criminalization of sex work and sex workers' vulnerability to HIV.…”
mentioning
confidence: 99%
“…" Prestage et al (2014) found that higher rates of unprotected anal intercourse (UAIC) among men sex workers and their clients are to be attributed to an ethic of sexual adventure and not to sex work itself. Their research revealed that both men sex workers and their clients are "more sexually active and adventurous in general than other men, and were more likely to have engaged in sex partying and group sex, including in the context of drug use," and that there are "strong associations between being sexually adventurous, engaging in intensive sex partying, and reporting UAIC" (Prestage et al 2014(Prestage et al , p. 1297.…”
mentioning
confidence: 99%
See 1 more Smart Citation